Settlement of Traffic Offences: A Shift in the Presumption of Innocence and the Impact on Legal Justice - Beny Harkat; Nandang Sambas; Chepi Ali Firman Zakaria (Borong Newinera Publisher, 2024)
Traffic offences are a serious issue in Indonesia, creating complex challenges for the justice system and social costs. Although Law No. 22/2009 has defined the rules, the high number of accidents and offences indicates the ineffectiveness of law enforcement. This study aims to investigate the impact of traffic offences on legal justice, the effectiveness of sanctions, and the shifting presumption of innocence in Indonesia. The research methodology included both quantitative and qualitative approaches, involving analyses of accident data and interviews with authorities. The results showed a high number of offences, a lack of effectiveness of Law No. 22 of 2009, and the phenomenon of